2020
DOI: 10.1007/s11136-020-02455-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymphedema self-management group-based education compared with social network-based education on quality of life and fear of cancer recurrence in women with breast cancer: a randomized controlled clinical trial

Abstract: Background Breast cancer-related lymphedema (BCRL) and its associated symptoms harm the quality of life (QoL) of cancer survivors and can stimulate fear of cancer recurrence (FCR). Self-management education for lymphedema has been introduced as an effective method in controlling FCR. This study investigates the effect of lymphedema group-based education compared to the social network-based and control group on QoL and FCR in breast cancer patients. Methods This three-arm clinical trial studied 105 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 39 publications
1
95
0
1
Order By: Relevance
“…The literature has demonstrated that heightened psychological distress, depression, and anxiety are associated with the development of lymphedema after cancer [ 3 , 4 ]. These psychological sequelae are often linked to feelings of hopelessness, fear of the future and isolation due to immobility, social avoidance, and/or sexual dysfunction [ 4 , 5 , 6 ]. As a result of the skin changes and swelling associated with lymphedema, cancer survivors have also reported the negative impact of this condition on their appearance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has demonstrated that heightened psychological distress, depression, and anxiety are associated with the development of lymphedema after cancer [ 3 , 4 ]. These psychological sequelae are often linked to feelings of hopelessness, fear of the future and isolation due to immobility, social avoidance, and/or sexual dysfunction [ 4 , 5 , 6 ]. As a result of the skin changes and swelling associated with lymphedema, cancer survivors have also reported the negative impact of this condition on their appearance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review showed that 29% of the texts studied [ 20 , 22 , 28 , 29 , 34 , 37 , 40 , 47 , 54 , 55 , 57 ] reported technological tools as a digital literacy alternative for people with health conditions, as well as for professionals, family members, and caregivers. Technological tools accessible to the community were identified using free applications, such as WhatsApp and WeChat, accessible via smartphone, and disseminating content through websites and social networks, defined as Digital Health Interventions (DHI).…”
Section: Resultsmentioning
confidence: 99%
“…Physiotherapy in Breast and Gynecological Cancer self-dressing for cases of absence of cutaneous lesion on the limb or when the patient or caregiver is insecure or unable to perform bandaging. The prescription of compression garments should be done with strict control of limb measurements [23][24][25] . d. Provide guidance regarding signs of worsening of lymphedema (pain, increased limb volume, altered sensitivity and changes in the skin) and the presence of inflammatory signs.…”
Section: Recommendations For Telephysiotherapy Follow-up In the Most Prevalent Complications I -Lymphedemamentioning
confidence: 99%
“…All the articles used the Disability Arm, Shoulder and Hand (DASH) Questionnaire to evaluate functionality. a. Assess the presence of postural changes, such as asymmetry of shoulders (elevation, depression and protrusion) and hip (inclination, rotation, ante or retroversion); and the range of motion of the upper or lower limbs 24 . b.…”
Section: -Functional Disabilitymentioning
confidence: 99%